2020
DOI: 10.1097/mop.0000000000000843
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based strategies to increase vaccination uptake: a review

Abstract: Purpose of review To summarize evidence-based strategies for improving pediatric immunization rates including physician behaviors, clinic and public health processes, community-based and parent-focused interventions, and legal and policy approaches Recent findings Studies continue to show the effectiveness of audit and feedback, provider reminders, standing orders, and reminder/recall to increase immunization rates. Provider communication strategies may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 122 publications
2
36
0
Order By: Relevance
“…All HCP should be familiar with indications for immunization 14 and evidence-based interventions that improve vaccine coverage (eg, standing orders, patient reminders/recall for vaccination, and provider reminders). 12,15 Furthermore, HCP should be aware of common concerns regarding immunization (eg, vaccine will cause disease due to antigen in the vaccine, lack of effectiveness, and safety), and they should be prepared to allay these concerns. Videos such as those available from the American Academy of Pediatrics (https://www.aap.org/en-us/advocacy-and-policy/aaphealth-initiatives/immunizations/Pages/Communication-Aids.…”
Section: Policy Statementsmentioning
confidence: 99%
“…All HCP should be familiar with indications for immunization 14 and evidence-based interventions that improve vaccine coverage (eg, standing orders, patient reminders/recall for vaccination, and provider reminders). 12,15 Furthermore, HCP should be aware of common concerns regarding immunization (eg, vaccine will cause disease due to antigen in the vaccine, lack of effectiveness, and safety), and they should be prepared to allay these concerns. Videos such as those available from the American Academy of Pediatrics (https://www.aap.org/en-us/advocacy-and-policy/aaphealth-initiatives/immunizations/Pages/Communication-Aids.…”
Section: Policy Statementsmentioning
confidence: 99%
“… 57 Recent reviews also identify multiple interventions that have shown success in addressing hesitancy directly with patients or indirectly through support of clinicians. 58 , 59 Many of these interventions and strategies focus on supporting successful provider-patient communication about vaccines and building a culture of immunization support through practice-level activities and systems. 60 …”
Section: Addressing Vaccine Hesitancymentioning
confidence: 99%
“…Healthcare provider recommendation is a well-researched strategy for increasing vaccine uptake in children. 22,[26][27][28][29] In order for healthcare providers to make an effective vaccine recommendation, it is necessary to inform, prompt and provide educational training and resources to providers about evolving COVID-19 vaccine recommendations and the rationale for vaccinating children and youth. 16,[30][31][32][33][34][35][36][37][38][39] It may be helpful to partner with primary care providers to administer vaccines in their offices, 40 and ensure parents are supported to have adequate paid time off for their children's appointments.…”
Section: Healthcare Provider Recommendationmentioning
confidence: 99%
“…To maximize impactful communication with parents, the use of shared decision-making and motivational interviewing techniques have been identified as useful strategies. 17,29,42,43…”
Section: Healthcare Provider Recommendationmentioning
confidence: 99%
See 1 more Smart Citation